Rehabilitation of patients with acquired maxillomandibular anomalies after surgical correction of disorders of the vestibule of the mouth - Makhlynets , N.P.; Ozhogan , Z.R.; Prots , G.B.; Yatsynovych, V.I.; Pyuryk , M.V. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Treatment of surgical wounds in patients with maxillomandibular anomalies is important after buccal frenum plastic surgery is relevant. Objective. Increasing the effectiveness of medical treatment of patients with a pathological bite after buccal frenulum plastic surgery. Methods. 30 patients were examined and treated. The patients underwent surgical correction of violations of the architecture of the oral cavity (buccal frenums) using the proposed method and palatal allografts. Patients of the I group (15 people) in the postoperative period were prescribed standard treatment, patients of the II group (15 people) were treated with a supplement based on hyaluronic acid. A clinical study was conducted, where the main point was to determine the height of attachment of the buccal frenulum and labial frenulum, the presence of changes in the periodontal tissues based on the results of the index assessment. They studied the condition of the surgical wound and the processes of the formation of a postoperative scar, performed a cytological examination of the mucous membrane according to H.V.Banchenko. Results. Before treatment, all patients were diagnosed with a violation of the architecture of the vestibule of the mouth, manifested by high-attached buccal frenums and labial frenums on the mandible (less than 5 mm); low-attached buccal frenums and labial frenums on the maxilla (less than 5 mm). In patients of the II group, a significant difference was observed in the index assessment of periodontal tissues and cytological characteristics (p≤0.05) and the formation of a normotrophic scar. They did not cause a traumatic effect on the periodontal tissues, the position of a separate group of teeth. After treatment, a significant difference in cytological characteristics and the phenomenon of “creeping attachment” was observed in patients of the II group compared to I group (p≤0.05). Conclusion. Surgical correction of the vestibule of the mouth is an important step in the complex treatment of patients with maxillomandibular anomalies. Cytological characteristics of the mucous membrane of the vestibule of the mouth and clinical characteristics of the postoperative scar indicate the advantages of using gengigel in the postoperative period.